ZnBr2-SiO2 catalyzed green synthesis of tetrazoles: Molecular docking and antioxidant activity studies - Reddivari, Chenna Krishna Reddy; Devineni, Subba Rao; Venkateshwarulu, Jyothi Kumar Malaka; Baki, Vijaya Bhaskar; Chippada, Appa Rao; Wudayagiri, Rajendra; Venkata, Rami Reddy Yallala; Chamarthi, Naga Raju (European Journal of Chemistry, 2017)
A series of 5-substituted and 1,5-disubstituted tetrazoles were synthesized in high yields from various biologically active substituted nitriles with sodium azide under heterogeneous catalysed (ZnBr2-SiO2) [2+3] cycloaddition conditions. This reaction gave an excellent yield in the presence of catalytic amount of 0.2 g of ZnBr2-SiO2, glycerol solvent system under microwave irradiation conditions. All the prepared compounds were characterized by elemental analysis 1H NMR, 13C NMR, FT-IR, and mass spectral data. The newly synthesized compounds were investigated for their respective molecular target using molecular docking studies. The results reveal that compounds 5a, 5c, 5e and 3e have conferred with multi target property. The compounds 5a, 5c and 5e have shown the highest binding affinities of -10.1, -9.7 and -10.6 with reverse transcriptase, -8.5, -8.2 and -8.9 with Aurora B, respectively. The compounds 5a, 5e and 3e have shown -8.9, -8.5 and 8.4 with Aromatase, respectively. In addition, the antioxidant activity data reveals that all the compounds showed good antioxidant activity, particularly the compounds 3d, 5d, and 5e exhibited promising radical scavenging activity.